Coaching en las organizaciones: experiencia con personal administrativo en salud - Mejía Chiang, César (2020)
Health sector organizations face problems of interrelation, stress and lack of motivation of the personnel, derived from the complexity of their tasks, structure, processes, and internal culture, which are the result of a disarticulated and disorganized national health system. To face these problems, talent management has become an element that generates value to create and promote new projects, create a good work environment, boost services, and generate customer satisfaction and loyalty, and commitment from the employees. Coaching has become a useful tool to establish a favorable work environment for the productive performance of employees. In this sense, the purpose of the study is to understand how coaching is implemented in an administrative staff in a Peruvian clinic. The aspects that contributed the most to an effective implementation were the style of the program, the connection between the coach and the coachee, the coach’s values and competencies, the presence of the organization, the perception of usefulness, and the ease of application.